"Was I asking for it?": An experimental investigation of perceived responsibility, mental contamination and workplace sexual harassment. (June 2021) - Krause, Sandra; Radomsky, Adam S.
Abstract: Background and objectives: Mental contamination (i.e., contamination concerns that arise in the absence of direct contact with a contaminant) is a common symptom in obsessive-compulsive disorder (OCD). Cognitive theories suggest that it results from individuals' misinterpretations of perceived violations. Cognitive theories of OCD also highlight the importance of appraisals of inflated responsibility in the maintenance of other OCD symptoms. However, the role of responsibility in mental contamination has not yet been examined experimentally. The present study examined the role of perceived responsibility and violation in the relationship between workplace sexual harassment imagery and subsequent mental contamination. Methods: One hundred and forty-nine participants listened to a workplace sexual harassment imagery task, wherein responsibility was manipulated. Participants were randomly assigned to one of three conditions (high responsibility (HR), low responsibility (LR), no responsibility (NR)). Participants completed questionnaires assessing mental contamination and completed a hand washing task. Results: Those in the NR condition reported significantly lower levels of responsibility than those in the LR or HR conditions. Accordingly, those in the NR condition also reported significantly lower levels of anxiety and dirtiness than in the LR condition. There were no significant differences between the LR and HR condition on variables of interest. Limitations: The nature of the victim blaming used for the responsibility induction may have elicited compensatory responses from participants. Conclusions: Findings may highlight the central role of perceptions of violation in the understanding and treatment of mental contamination. Highlights: Responsibility was experimentally manipulated in the context of mental contamination. The study used an adaptation of the dirty kiss paradigm, involving sexual harassment. Harassment, without contact contamination confounds, evoked mental contamination. Perceptions of violation better predicted mental contamination than responsibility. No differences in washing behaviour were observed.